Kompleksitas Praktik Kewarisan Islam Di Indonesia: Sebuah Telaah Interdisipliner - Mushlih Candrakusuma; Rudi Purnomo (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
The practice of Islamic inheritance in Indonesia demonstrates a high level of complexity due to the interaction between Sharīʿah norms, positive law, customary practices, and evolving social realities. Although Islamic inheritance law is normatively well established in the Qur’an, Hadith, and classical fiqh al-mawārīth, its implementation in Indonesia cannot be separated from the country’s plural legal system, particularly through the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) and the practice of religious courts. In addition, modern family dynamics, local cultural diversity, and administrative as well as technical requirements significantly influence inheritance distribution in practice. This research aims to examine the complexity of Islamic inheritance practices in Indonesia through an interdisciplinary approach that integrates perspectives from Islamic law, positive law, and supporting disciplines. A qualitative method with a library research design is employed, drawing on primary and secondary legal materials and a socio-legal analysis of inheritance practices in society. The analysis applies normative and comparative approaches to explore the relationship between ideal Sharīʿah provisions and empirical realities. The findings indicate that Islamic inheritance is not merely a normative–fiqh issue but also involves intertwined juridical, social, and technical dimensions. The involvement of auditing, asset appraisal, medical, and notarial expertise is essential to ensuring justice, accountability, and legal certainty. Therefore, an integrative interdisciplinary approach is indispensable for strengthening Islamic inheritance governance in Indonesia.